Efforts of Islamic Education Teachers to Foster Learning Motivation Among Senior High School Students - Anisa, Anisa; Akmal, Fauzi; Afrianto, Afrianto (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
This article discusses the efforts of Islamic Education teachers in fostering learning motivation among students at the senior high school level. The teacher's role is crucial in creating a conducive and inspiring learning environment. The study aims to identify the strategies implemented by Islamic Education teachers to enhance students’ enthusiasm for learning and to evaluate the effectiveness of the approaches used. The methodology employed is qualitative research in the form of a case study, conducted through classroom observation, interviews, and documentation of teaching practices. The findings reveal that Islamic Education teachers at the senior high school level strive to build students’ learning motivation through several effective strategies, including implementing fair and transparent assessments, where students understand the evaluation criteria and feel appreciated for their efforts. Teachers also provide rewards or praise for students’ achievements, both verbally and symbolically, as a form of appreciation that encourages learning enthusiasm. Additionally, teachers create a healthy competitive atmosphere through quizzes or contests related to the subject matter, motivating students to be more active, confident, and engaged in the Islamic Education learning process.